Sport burnout inventory–Dual career form for student-athletes: Assessing validity and reliability in a Finnish sample of adolescent athletes - Matilda Sorkkila; Tatiana V. Ryba; Kaisa Aunola; Harri Selänne; Katariina Salmela-Aro (Journal of Sport and Health Science, 2020)
Background: The pressure of pursuing an athletic career simultaneously with education may set adolescent student-athletes at risk for sport and school burnout. Although the 2 life domains of student-athletes are strongly intertwined, so far, there has not been an instrument for investigating sport burnout parallel to school burnout. The aim of the present study was to introduce a sport burnout measure for adolescents in a dual career context and investigate its validity and reliability by using confirmatory factor analysis. Methods: The participants were 391 student-athletes (51% females) who filled in a questionnaire of sport burnout and background variables in the beginning of upper secondary school. Results: A 3-factor model or a second-order-factor model described the data better and gave better reliability indices than a 1-factor model. The 3 dimensions of sport burnout were shown to be separate, but closely related constructs. Evidence for convergent and discriminant validity was obtained by correlating the 3 sport burnout dimensions with depressive symptoms, self-esteem, and sport task values. Conclusion: The results suggest that Sport Burnout Inventory–Dual Career Form (SpBI-DC) is a valid and reliable instrument for investigating sport burnout among adolescent student-athletes.